2002
DOI: 10.1159/000049350
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control Orientation in Panic Disorder and the Differential Effects of Treatment

Abstract: Background: In this study the effects of treatment with cognitive therapy, antidepressants or pill-placebo on the locus of control orientation in panic disorder patients were analysed, as well as the relation of this panic locus of control with panic frequency and cognitive measures of panic. Methods: A Multidimensional Anxiety Locus of Control scale (MALC) was developed and completed with other measures (ACQ and BSQ) before and after treatment. Patients also kept a panic diary. Results: Four subscales were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…We were especially interested in the possible influence of locus of control orientation (a multidimensional concept indicating a patient's beliefs about the controllability of the panic disorder) on differential effectiveness of the two treatment groups. As Bakker, Spinhoven, van der Does, van Balkom, and van Dyck (2002) concluded, "another interesting question that needs further research is the possibility that locus of control orientation constitutes a prescriptive indicator, that is, a variable predicting differential response to one versus another treatment" (p. 61).…”
Section: Real Data Example: the Treatment Of Panic Disorder Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We were especially interested in the possible influence of locus of control orientation (a multidimensional concept indicating a patient's beliefs about the controllability of the panic disorder) on differential effectiveness of the two treatment groups. As Bakker, Spinhoven, van der Does, van Balkom, and van Dyck (2002) concluded, "another interesting question that needs further research is the possibility that locus of control orientation constitutes a prescriptive indicator, that is, a variable predicting differential response to one versus another treatment" (p. 61).…”
Section: Real Data Example: the Treatment Of Panic Disorder Studymentioning
confidence: 99%
“…All locus of control scales were measured by the Multidimensional Anxiety Locus of Control scale (MALC; Bakker et al, 2002). We recoded the four locus of control scales described by Bakker et al (2002) in such a way that a higher score on a scale indicated a higher specific locus of control. In addition, De-test Anxiety was used as a covariate, and Post-test Anxiety was the outcome variable (y; both variables were measured by the HAMA).…”
Section: Real Data Example: the Treatment Of Panic Disorder Studymentioning
confidence: 99%
“…In addition, it has been emphasized that enhancing mastery and confidence in self-control are important ingredients in anxiety management treatments [11]. LOC evolved from a general concept indicating a person’s expectation about how reinforcement is controlled [12] to more specific concepts, for example, a patient’s beliefs about the controllability of an anxiety disorder (the Multidimensional Anxiety Locus of Control scale [13]). Liberman [14] investigated the influence of LOC in a small sample of psychiatric outpatients who were referred for psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This method finds one or more optimal thresholds on a predictor variable. Internal LOC and medication LOC are two of the four subscales measured by the Multidimensional Anxiety Locus of Control Scale [13]. We were also interested in the possible influence of the other two subscales (therapist LOC and chance LOC).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Finally, cognitive behavioral therapy and other psychotherapeutic interventions have proven efficacy with both PD and MDD. [25][26] Aims of the study: 1-To estimate the frequency of agoraphobia in PD and the related sex difference. 2-To estimate the comorbidity rate of MDD in PD and the related sex difference.…”
mentioning
confidence: 99%